1998
DOI: 10.1023/a:1007554726449
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Knowledge of the prevalence of congenital cytomegalovirus infection is necessary to evaluate the need for prevention. We performed a multicentre one-year study involving 11 neonatology divisions to ascertain the prevalence in Lombardy. Cytomegalovirus was isolated by culturing saliva samples from all babies born (n = 1268) of two 15-day sample periods and from 185 neonates with suspected congenital CMV based on clinical and laboratory findings and the history. The overall prevalence of congenital infection was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Four of the 15 studies were considered to having a low risk of bias in any of the domains [ 2 , 15 , 21 ]. Nine studies were assessed as having a high risk of patient selection bias, because the neonates with classical symptoms of cCMV infection, confirmed using reference standard might have been more easily diagnosed with cCMV [ 10 - 12 , 14 , 22 - 26 ]. Seven studies (5 with high risks and 2 with unclear risks) were identified as high risks in the index test domains [ 12 - 14 , 16 , 22 , 23 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four of the 15 studies were considered to having a low risk of bias in any of the domains [ 2 , 15 , 21 ]. Nine studies were assessed as having a high risk of patient selection bias, because the neonates with classical symptoms of cCMV infection, confirmed using reference standard might have been more easily diagnosed with cCMV [ 10 - 12 , 14 , 22 - 26 ]. Seven studies (5 with high risks and 2 with unclear risks) were identified as high risks in the index test domains [ 12 - 14 , 16 , 22 , 23 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…A subgroup analysis of the study design (Table 5 a) was performed because the 7 prospective studies [ 2 , 10 , 13 , 15 , 21 , 26 ] had lower sensitivity than the retrospective studies [ 11 , 12 , 14 , 16 , 22 - 25 ]. The results showed that the 7 prospective studies, with no significant heterogeneity had obviously lower sensitivity (0.623) than the retrospective studies (0.945).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the risk of fetal damage is greater if the primary infection occurs during the first trimester of pregnancy 46. The prevalence of congenital infection ranges from 0.2% to 2.5% in different populations,713 with groups at greater risk including Black or Asian women, those from a low socioeconomic background, and those that are born prematurely 10…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of congenital infection ranges from 0.2% to 2.5% in different populations [1420], in which the risk factors include particular races or ethnic groups, a low socioeconomic status, premature birth, and admission to an intensive care unit [6, 17]. Furthermore, the prevalence of congenital infection varies with the prevalence of the infection in the population [21].…”
Section: Introductionmentioning
confidence: 99%